AN EVALUATION ON ESP TEXTBOOK ENTITLED “BAHASA INGGRIS UNTUK MARITIM DAN PERIKANAN”: STUDENTS’ PERSPECTIVES AT SMK ARUNG SAMUDERA BANJARMASIN - Anisa Yulia Nabilah; Rina Listia; Noor Eka Chandra (UICELL, 2022)
The types of schools in Indonesia are various, as they have their characteristics. Vocational schools, as one of the school types, should get attention from specific materials such as ESP textbooks related to their field. In purpose to determine how successful the role of ESP textbooks is in a particular school, a term called evaluation is needed. It is significant in classroom circumstances because it can help teachers or stakeholders consider the existence and effectiveness of the textbook. To collect the data, a qualitative study was used because the data deals with respondents’ perspectives. The researcher conducted the research in SMK Arung Samudera Banjarmasin, and ten students of 2021/2022 roled as the participants in this study, at the end of their first semester. The instruments were questionnaires as the basis of data and the interview to complete the students’ perspectives. The results indicated satisfying results. From the total of 22 questions in the questionnaire, divided into four criteria, all of them obtained good or excellent scores. The results from the questionnaire are justified by interview results. In addition, the purpose meets students’ needs, content, and language exercise contain ESP real context. Besides, the skills in the textbook are integrated, various, and support their field, and the strategies for the learning process also suitable for students. Even though this study indicated satisfying results, however, it was conducted on a small population, so similar answers and data are likely to appear. The next researcher can investigate the wider population to get various perspectives. Keywords: Evaluation, ESP textbook, SMK